Diseño de un proceso para la producción de abono orgánico a partir de lodos residuales generados en la PTAR del municipio de Funza, Cundinamarca. (2022)
In the production of organic fertilizer, starting from the sludge generated in the wastewater treatment plant of the municipality of Funza-Cundinamarca, the physicochemical characterization of the sludge obtained was carried out, for the selection of the appropriate system a multicriteria matrix "Pugh" was used, the criteria evaluated were: costs, efficiency, required area and retention time of the material. The selected process is a horizontal reactor with overturning, where bulking agents are required to supply the composting needs. For the design of the process, the balance of matter was applied, which includes variables such as C/N ratio and humidity of the system. During the experimentation, the variables of temperature, humidity, pH and ash were analyzed at the beginning and end of the process for the raw material; the compost obtained was analyzed in an external laboratory where it was found to comply with the requirements specified in NTC 5167 (2011). Likewise, for the bulking agent, the characterization was carried out by means of a literature review. On the other hand, the scaling of the pilot scale prototype of a horizontal reactor was carried out in order to establish its dimensions and technical specifications for production. In the analysis of operating and investment costs, criteria such as income, direct and indirect costs were included, during the Cost/Benefit ratio it was identified that the project is feasible.